ANALISIS PENGUKURAN KINERJA GREEN SUPPLY CHAIN MANAGEMENT PADA PERUSAHAAN PELAPISAN LOGAM DENGAN PENDEKATAN GREEN SCOR - Frederick S C, Lamberth; Saryatmo, Mohammad Agung; Doaly, Carla O (Universitas Tarumanagara, 2025)
Metal plating and stamping companies face greater challenges in managing waste, energy consumption, and selecting environmentally friendly raw materials. Therefore, the performance of Green Supply Chain Management (GSCM) is crucial to support the sustainability of business operations. This study aims to analyze the GSCM performance in a metal plating and stamping company by using an integrative method combining Green SCOR, Analytical Hierarchy Process (AHP), Objective Matrix (OMAX), and the Traffic Light System (TLS). The Green SCOR model is used to identify the five main processes in the supply chain, AHP is used to determine the priority weights of each performance indicator, and OMAX is applied to measure and evaluate the company’s actual GSCM performance. The results of the study identify which indicators within the overall supply chain process require improvement. Based on the findings, 12 indicators fall into the green category, 2 indicators are categorized as yellow, and 7 indicators are categorized as red. The yellow and red indicators need to be improved in order to enhance the company’s future GSCM performance.